Analytical investigation of the interfacial behavior of a prestressed concrete beam strengthened with a prestressed FRP-bonded plate - Mebsout, Hanane; Benatta, Mohamed Atif; Krour, Baghdad; Benachour, Oussama; Bachir Bouiadjra, Mohamed; Rahal, Nacer (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Utilizing composite materials to reinforce reinforced concrete structures is now a very prevalent practice in the field of civil engineering. However, prestressed concrete construction does not usually use this method. The principal purpose of the present study is to extend the use of composite materials to reinforce prestressed concrete beams by taking into account the effect of interfacial stresses concentration on the global behavior of such structures. Methods: A new analytical model is suggested taking into account how changes in the RC beam’s prestress affect the interface stresses. A polynomial function expressing the variation of the geometrical shape of the cable as well as the instantaneous and non-instantaneous losses of the prestressed concrete beam is considered in order to address the issue of stress concentration at the adhesive-plate-concrete interface. Results: The main findings of the present investigation demonstrate that, in the presence of cable prestress, the interface stresses decrease non-significantly; but, as the prestressing force applied to the FRP plate increases, a more substantial increase of interfacial stresses is observed. Conclusion: Because of a high degree of contact stresses at the plate end the debonding risk becomes greater and an anchoring mechanism is recommended at the edge of the plate.